대학병원 간호사의 정신건강에 영향을 미치는 요인 - 윤성자(Sung-Ja Yoon); 황주희(Ju-Hee Hwang); 박은하(Eun-Ha Park); 최명희(Myeong-Hui Choe) (디지털콘텐츠학회논문지, 2019)
본 연구는 간호사의 직무스트레스를 고려한 상태에서 성격특성과 회복탄력성이 이들의 정신건강에 미치는 영향을 파악하기 위해 시행되었다. 연구대상자는 대학병원에 근무하는 간호사 205명이었으며, 2019년 5월 중 설문조사를 실시하였다. 연구의 결과는 다음과 같다. 일반적 특성 중 성별과 주관적 신체건강인식이 정신건강과 관련이 있었으며, 설명력은 15.1% 이었다. 직무스트레스의 설명력은 17.2%였고, 직무스트레스가 증가할수록 정신건강이 나빠졌다. 정신건강에 대한 회복탄력성의 설명력은 7.4%였고, 회복탄력성이 증가할수록 정신건강이 좋아지는 것을 확인하였다. 성격특성의 모든 유형이 정신건강과 관련이 있었고, 정신건강의 8.7%를 설명하였다. 따라서 간호사의 정신건강증진을 위하여 직무스트레스를 줄이고 회복탄력성을 향상시킬 수 있는 중재 프로그램이 필요하다. 또한 프로그램 대상자 선정시 간호사들의 성별, 주관적 신체건강인식과 성격유형을 고려하여야 한다. The purpose of this study was to identify the effects of personality traits and resilience on their mental health in consideration of occupational stress of nurses. The subjects were 205 nurses working at university hospitals and conducted a questionnaire survey in May, 2019. The results of the study are as follows. Among general characteristics, gender and subjective perception of physical health were related to mental health and explained mental health by 15.1%. Occupational stress explained 17.2% of mental health and mental health was worse as occupational stress increased. The explanatory power of resilience to mental health was 7.4%, and it was confirmed that mental health was improved as resilience increased. All types of personality types were associated with mental health and explained 8.7% of mental health. Therefore, intervention programs for reducing occupational stress and improving resilience in nurses are required to promote their mental health. Also, nurses' gender, subjective perception of physical health, and personality type should be considered when choosing program participants. KCI Citation Count: 7